2003
DOI: 10.1073/pnas.1632821100
|View full text |Cite
|
Sign up to set email alerts
|

A chemical approach for identifying O -GlcNAc-modified proteins in cells

Abstract: The glycosylation of serine and threonine residues with a single GlcNAc moiety is a dynamic posttranslational modification of many nuclear and cytoplasmic proteins. We describe a chemical strategy directed toward identifying O-GlcNAc-modified proteins from living cells or proteins modified in vitro. We demonstrate, in vitro, that each enzyme in the hexosamine salvage pathway, and the enzymes that affect this dynamic modification (UDP-GlcNAc:polypeptidtyltransferase and O-GlcNAcase), tolerate analogues of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
422
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(432 citation statements)
references
References 42 publications
6
422
1
3
Order By: Relevance
“…The tag provides both a straightforward means to enrich low-abundance O-GlcNAc peptides from complex mixtures and a unique signature upon MS͞MS for unambiguous identification of the O-GlcNAc-glycosylated species. In contrast to reported antibody, lectin, and metabolic labeling methods (11)(12)(13), the strategy provides direct evidence of OGlcNAc glycosylation and permits mapping of modification sites to short amino acid sequences. The ability to localize O-GlcNAc is essential for surveying its distribution across the proteome and understanding its functional significance on a given protein or family of proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tag provides both a straightforward means to enrich low-abundance O-GlcNAc peptides from complex mixtures and a unique signature upon MS͞MS for unambiguous identification of the O-GlcNAc-glycosylated species. In contrast to reported antibody, lectin, and metabolic labeling methods (11)(12)(13), the strategy provides direct evidence of OGlcNAc glycosylation and permits mapping of modification sites to short amino acid sequences. The ability to localize O-GlcNAc is essential for surveying its distribution across the proteome and understanding its functional significance on a given protein or family of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins have been tritiumlabeled (10), enriched with lectins or antibodies (11,12), or chemically tagged by metabolic labeling or BEMAD (␤-elimination followed by Michael addition with DTT) (12,13). However, none of the existing methods is ideally suited to the direct, highthroughput identification of O-GlcNAc proteins from tissues or cell lysates.…”
mentioning
confidence: 99%
“…This technique has been adapted for the detection and enrichment of O-GlcNAc-modified proteins and peptides. Sugars containing either ketones or azido groups are incorporated into O-GlcNAc-modified proteins using one of two techniques: (1) a mutant GalT1 (Y289L) with an enlarged active site is used to add UDP-GalNAz to terminal GlcNAc residues similar to the GalT1 labeling discussed above (Khidekel et al 2003); and (2) in cells by metabolic labeling with a peracetylated azido-GlcNAc substrate (Vocadlo et al 2003;Sprung et al 2005), as many of the enzymes in the HBP will tolerate unnatural sugars. However, the kinetics of O-GlcNAz removal from proteins by OGlcNAcase is significantly reduced.…”
Section: Hek293t Cells Ion Trap Etd Ms/msmentioning
confidence: 99%
“…A complementary strategy involves tagging O-GlcNAc-modified proteins through metabolic labeling of living cells with N-azido-acetylglucosamine (GlcNAz) 87 . Vocadlo and co-workers showed that the azido sugar is processed by enzymes in the hexosamine salvage pathway and forms O-GlcNAz-modified proteins.…”
Section: Rapid Sensitive Detectionmentioning
confidence: 99%